Study on Machining Process of Multi-step Holes by Using The Standard Cutting Tool and Stepped Drill - V. L. Trinh; T. S. Nguyen; K. T. Chu; V. H. Tran (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2026)
Besides technological solutions, machining productivity is a factor that it is always considered by manufacturers. The cutting tool (CT) is one of the key points to boost the cutting efficiency and improve machining productivity of the machining process. The proper cutting tool is a good solution for saving the cutting time, enhancing the machining quality, and improving the time life of machine tools. Traditional drilling method uses a standard cutting tool (SCT) with single cutting diameter that revealed disadvantages of low cutting velocity and high cost. This paper demonstrates a method of using the combination cutting tool (CCT)that equipped more cutting diameters in the same knife body to enhance machining productivity and reduce cutting time during drilling multi-step holes. By introducing a CCT, the machining productivity increases of about 131.72% and 257.9% in comparison to the CC in the option 1 and option 2, the cutting time deceases of about 72.06% and 56.85% in comparison to the CC in the option 1 and option 2, and the technology cost decreases of about 42.86% and 63.64% in comparison to the CC in the option 1 and option 2, respectively. The results show that the combination cutting tool is a good solution to improve the machining productivity and cost effectiveness during machining multi-step holes.